EDITORIAL - Franco Vásquez, José Gabriel (Medicina UPB, 2024)
The first issue of Medicina UPB in 2024 features a variety of articles that may be of interest to healthcare professionals; several of them focus on women’s health. In total, it contains five original research articles, four narrative reviews, and two case reports.